Roman Table-Legs in Northern Italy. Figurative monopodia (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2022)
Table-Legs (trapezophoroi) are one of the most characteristic pieces of furniture in Roman residences, where they are found in a great variety of forms and types. Monopodia with human figures represent the most refined and sought-after category of the class, appearing as true sculptures, albeit small in size, which are inserted into the domestic figurative universe, contributing to enriching its iconographic and visual imagery. These dynamics can also be observed in Northern Italy, despite the limited number of known attestations, testifying the reception in this area of artistic and cultural instances that were widespread in the Roman world.
Keywords: Table-Legs; monopodia; domestic furniture; domus